SOSIALISASI KESEHATAN MENTAL PADA IBU RUMAH TANGGA DAN IBU KARIR DI DESA MALAKASARI - Rahmani, Annisa; Fauziyyah, Hana; Mustika Pamungkas3, Jaka; Farid Roihan, Muhammad; Dwi Sulistia Putri, Nadila; Zulbetti, Rita (JURNAL PENGABDIAN KEPADA MASYARAKAT (ADI DHARMA), 2023)
Abstract Mental health is a very important aspect for the well-being of oneself and one's family, but is often neglected in everyday life. No exception for a mother, a mother's mental health can affect family conditions and child rearing patterns. According to mental health specialists, mental health problems that often occur in mothers are stress, depression and anxiety disorders. Mental health problems in working mothers can be caused by multiple responsibilities in their roles as wives, mothers and career women. Meanwhile, for housewives, mental health problems can be caused by activities that feel like they never end and recurring problems that are not handled appropriately. In one of our community service activities, we held outreach regarding mental health for housewives and career mothers with the aim of socializing and increasing understanding of housewives and career mothers about the importance of caring for mental health. The targets of this service activity are housewives who attend Integrated Healthcare Center activities in Malakasari Village. The data collection method uses the literature study method, this socialization activity is carried out using lecture, evaluation and question and answer methods. As a result of this outreach, it is hoped that mothers will be more aware and understand the importance of mental health in their role as mothers.